1946
DOI: 10.1021/ja01216a646
|View full text |Cite
|
Sign up to set email alerts
|

New Compounds. A New Acetylene Silver Nitrate Complex

Abstract: New Compounds 2745 added. The mixture was heated for fifteen minutes on a steam-bath and then diluted with 300 ml. of water. The precipitation and purification of the base was as described in method A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

1964
1964
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 0 publications
1
8
0
4
Order By: Relevance
“…[214] If only arene units are available for silver coordination in addition to the terminal alkynyl groups, and if there is a deficit in anion coordination, then the silver atoms entertain h 2 -bonding to the edges of phenyl rings to assist in their coordinative saturation. [203] Butterfly-type Ag 4 units have also been detected in the supramolecular aggregates produced from 4-pyridylethyne and CF 3 COOAg (1:6) or AgNO 3 (2:4) with structural patterns as shown in 65. The compounds are strongly luminescent in the solid state (l em = 564 and 610/556 and 620, l ex= 362/380 nm, respectively).…”
Section: Silver Clustering At Alkynyl Anions [(C C) N ] 2à [R-c C] mentioning
confidence: 94%
See 1 more Smart Citation
“…[214] If only arene units are available for silver coordination in addition to the terminal alkynyl groups, and if there is a deficit in anion coordination, then the silver atoms entertain h 2 -bonding to the edges of phenyl rings to assist in their coordinative saturation. [203] Butterfly-type Ag 4 units have also been detected in the supramolecular aggregates produced from 4-pyridylethyne and CF 3 COOAg (1:6) or AgNO 3 (2:4) with structural patterns as shown in 65. The compounds are strongly luminescent in the solid state (l em = 564 and 610/556 and 620, l ex= 362/380 nm, respectively).…”
Section: Silver Clustering At Alkynyl Anions [(C C) N ] 2à [R-c C] mentioning
confidence: 94%
“…In early structural work is had already been demonstrated that in crystals of the classical example (Ag 2 C 2 )(AgNO 3 ) 6 the C 2 dumbbell is surrounded by a rhombohedral Ag 8 cage ([C 2 @Ag 8 ] 6+ , 62 a). [203] In (Ag 2 C 2 )(AgNO 3 ) 5 , isolated from the same lot of crystals, the C 2 unit is accommodated in a trigonal prism monocapped at a square face or at a trigonal face ([C 2 @Ag 7 ] 5+ , 62 b, 62 c). [194,204] Dissolving Ag 2 C 2 in a concentrated aqueous solution of AgF produces a complex of the composition Ag 2 C 2 ·8 AgF in which the C 2 dumbbells are located in the center of a capped square antiprism (62 d) with one external silver atom on the fourfold axis (described as [{C 2 @Ag 9 }Ag] 8+ .…”
Section: Silver Clustering At the Acetylide Dianionmentioning
confidence: 99%
“…Darüber hinaus sind die Ketten wohl über eine Side-on-p-Koordination der Acetyleneinheiten an Metallatome und über argentophile Wechselwirkungen verknüpft. 1946 wurde beobachtet, [203] dass der Niederschlag in einer wässrigen Lçsung, die einen Überschuss an AgNO 3 enthält, unter Bildung eines "Doppelsalzes" (Ag 2 C 2 )(AgNO 3 ) 6 leicht lçslich ist, und in der Folge wurden verschiedene andere Produkte dieses Typs mit Silbersalzen mit anderen Anionen als Nitrat gefunden. Diese Befunde belegen, dass das [CC] 2À -Dianion eine starke Affinität zu Silberkationen hat, und in späteren Untersuchungen wurde gezeigt, dass seine mehrfache Versilberung zu einer faszinierenden Vielfalt an C 2 -zentrierten Silberclustern führt, die mit Formeln wie [C 2 @Ag n ] (nÀ2)+ (n = 6-10) beschrieben werden.…”
Section: Bildung Von Silberclustern Am Acetyliddianionunclassified
“…6AgNO 3. The 1 : 1 complex can also be made by reaction of the 1:6 complex with water (Shaw & Fisher, 1946).…”
Section: Crystallographic Data For Silver Acetylide a D R~dhovse Amentioning
confidence: 99%